PRODUÇÃO DE BIOGÁS DE DEJETOS DE AVES E OVINOS EM BIODIGESTORES ALTERNATIVOS TIPO BATELADA - Volpato, Tulio; Gonçalves, Matheus; Cappi, Nanci; De Almeida, Cristiane; Vaso, Larissa Maria; De Souza, Jonas (ANAIS DO ENIC, 2018)
-